2006
DOI: 10.1007/s10350-006-0502-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Physiologic Outcomes After Transvaginal Rectocele Repair

Abstract: Transvaginal rectocele repair can provide excellent long-term symptomatic relief and a high rate of patient satisfaction without any alteration in anorectal physiologic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Postoperative dyspareunia will occur in 25 percent of patients and at least 10 percent may recur and require reoperation; 36 percent will report a problem with fecal incontinence. [60][61][62][63] A prospective study of rectocele repair using xenograft has been reported. 64 Although significant decreases in rectal emptying difficulties were noted, cure of the rectal emptying difficulties was reported by less than half of the patients at the three-year follow-up.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Postoperative dyspareunia will occur in 25 percent of patients and at least 10 percent may recur and require reoperation; 36 percent will report a problem with fecal incontinence. [60][61][62][63] A prospective study of rectocele repair using xenograft has been reported. 64 Although significant decreases in rectal emptying difficulties were noted, cure of the rectal emptying difficulties was reported by less than half of the patients at the three-year follow-up.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…2 Although excellent functional results have been demonstrated with posterior colporrhaphy, postoperative dyspareunia has been reported in up to 20% of cases. [3][4][5][6] Colorectal surgeons typically prefer the transanal approach to rectocele repair, which provides the necessary exposure for repair of concurrent anorectal pathology. Anatomic and functional improvements with this technique have been described by many authors in both prospective and retrospective studies.…”
mentioning
confidence: 99%
“…16,17 Other studies have reported an improvement of constipation after surgery, supporting the concept that rectoceles may cause ODS. 1,18,19 This discrepancy may be explained by an underestimation of the posterior compartment and rectal intussusceptions, respectively, which are found in up to 60 percent in combination with anterior rectoceles. 6,7 This figure is even higher in our series (75 percent).…”
Section: Discussionmentioning
confidence: 87%